(untitled) (Paliativní medicína, 2023)
Introduction: In order to implement palliative care in the hospital, it is essential to educate staff about benefits of the palliative care team, to raise awareness of the service across t system, and to know the needs of the primary care team. The aim of this paper is to present the process of implementing palliative care in the setting of Thomayer University Hospital. Methodology: In October 2022, the Palliative Care Unit started to work for paediatric and adult patients. After half a year of work, an online questionnaire was sent out to assess the implementation. Results: 223 respondents completed the questionnaire from April to May 2023. In this population, 71% of respondents had worked with the team, and they rated their experience as mostly positive in 85%, valuing the improvement in care, help with symptom management, and improved communication with families. Almost a third of respondents had never worked with the team, 26% had no need to, and 3% had never heard of palliative care team. Respondents who have never worked with palliative care team agree that palliative care belongs to medicine and its development should be encouraged. Half of them are also concerned that patients may lose hope. Conclusion: The implementation seems to be successful, most respondents have heard of the team and know what palliative care means. The implementation process was supported by a number of steps - workshops, meetings with the heads of each clinic,and contact with the primary teams at each intervention.